2014
DOI: 10.1021/am501867b
|View full text |Cite
|
Sign up to set email alerts
|

Study of Factors Governing Oil–Water Separation Process Using TiO2 Films Prepared by Spray Deposition of Nanoparticle Dispersions

Abstract: Surfaces which possess extraordinary water attraction or repellency depend on surface energy, surface chemistry and nano-and microscale surface roughness. Synergistic superhydrophilic-underwater superoleophobic surfaces were fabricated by a spray deposition of nanostructured TiO 2 on stainless steel mesh substrates. The coated meshes were then used to study gravity driven oil-water separation, where only the water from the oil-water mixture is allowed to permeate through the mesh. Oil-water separation efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(101 citation statements)
references
References 41 publications
1
100
0
Order By: Relevance
“…Therefore, much attention was paid on developing facile methods for fast and selective removal of oils from water surface. A number of strategies have been proposed for achieving this goal, which mainly involved meshes [9][10][11][12][13], films [14,15], or membranes [16][17][18][19]. Although these previously developed materials can be effective for oil/water separation, they cannot be applied in the place of the oil spills because the polluted water should be first collected and then be filtered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much attention was paid on developing facile methods for fast and selective removal of oils from water surface. A number of strategies have been proposed for achieving this goal, which mainly involved meshes [9][10][11][12][13], films [14,15], or membranes [16][17][18][19]. Although these previously developed materials can be effective for oil/water separation, they cannot be applied in the place of the oil spills because the polluted water should be first collected and then be filtered.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the development of effective and inexpensive methods for oilwater separation has become an important issue in order to meet environmental and economic demands [1]. Despite the fact that many oil-water separation methods such as adhesion, membrane filtration, and absorbance have been developed and are widely used [2], achieving an energy-and cost-effective oil-water separator with high efficiency remains a great challenge. Since oil-water separation is governed by the interfacial features of the substrate, fabrication of preferential wettability materials toward oil or water is desirable and effective [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel materials possessing both hydrophobic/oleophilic ''oil-removing'' and hydrophilic/oleophobic ''water-removing'' surfaces have been developed, with which oil or water phases spread and penetrate readily through the material, and the remaining water or oil phase is repelled [2][3][4][5][6][7][8]. For a small oil spill, oil sorbent materials are commonly used, and recent studies have focused on the preparation of superhydrophobic sponges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high definition FESEM image (figure 1f) revealed that the nanowire hosts were uniformly and densely covered by 200nm long and 150nm wide nanosheet structures. This incorporation of nanosheet onto nanowire form a single "heterostructure" that possesses enhanced specific surface area for mass transfer and reactive sites, which are important factors to improve the photocatalytic properties as well as oil-water separation ability [37,38]. As shown in figure S1, the thickness of a typical TiO 2 nanostructured membrane is approximately 120µm.…”
mentioning
confidence: 99%